2021
DOI: 10.3389/fncel.2020.611379
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion Molecules Involved in Neurodevelopmental Pathways Implicated in 3p-Deletion Syndrome and Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is characterized by impaired social interaction, language delay and repetitive or restrictive behaviors. With increasing prevalence, ASD is currently estimated to affect 0.5–2.0% of the global population. However, its etiology remains unclear due to high genetic and phenotypic heterogeneity. Copy number variations (CNVs) are implicated in several forms of syndromic ASD and have been demonstrated to contribute toward ASD development by altering gene dosage and expression. Increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 213 publications
(395 reference statements)
1
25
0
Order By: Relevance
“…Notably, in hemideletion hCOs DPP6, RBFOX1, and TCERG1L were each downregulated in several cell types and are previously associated with ASD and attention-deficit hyperactive disorder (ADHD) (Figure 5) [68][69][70] . Furthermore, we found downregulated genes grouped across cell types that play a role in neuronal cell adhesion and were previously associated with ASD including CHL1, CNTN4, and NLGN1 [71][72][73][74] (Figure 5). Interestingly, independent studies showed pathogenic CNVs within RBFOX1, DPP6, CNTN4, NLGN1, and CHL1 in patients suffering from several different neurodevelopmental disorders 5,[75][76][77] .…”
Section: Cell-type Specific Alteration Of Gene Expression By 16p112 Hemideletionmentioning
confidence: 83%
“…Notably, in hemideletion hCOs DPP6, RBFOX1, and TCERG1L were each downregulated in several cell types and are previously associated with ASD and attention-deficit hyperactive disorder (ADHD) (Figure 5) [68][69][70] . Furthermore, we found downregulated genes grouped across cell types that play a role in neuronal cell adhesion and were previously associated with ASD including CHL1, CNTN4, and NLGN1 [71][72][73][74] (Figure 5). Interestingly, independent studies showed pathogenic CNVs within RBFOX1, DPP6, CNTN4, NLGN1, and CHL1 in patients suffering from several different neurodevelopmental disorders 5,[75][76][77] .…”
Section: Cell-type Specific Alteration Of Gene Expression By 16p112 Hemideletionmentioning
confidence: 83%
“…In humans three of the contactin family genes, CNTN3 , CNTN4 and CNTN6 are located on the short arm of the chromosome 3. Deletions in this region frequently result in the 3p-deletion syndrome – a genetic disorder associated with ASD, schizophrenia, epilepsy and accompanied by developmental delay and intellectual disability [ 10 ]. Copy number variations in 3p-deletion syndrome often occur at the 3p26 locus (which contains CNTN4 , CNTN6 ) and one case report of a child with a proximal interstitial 3p deletion that included CNTN3 (located at 3p12) also demonstrated neurodevelopmental delay, growth retardation and dysmorphic facial features among other abnormalities [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such structural similarity may confer overlapping and redundant functions on these CAMs. It has been observed that larger copy number variations, affecting multiple genes in 3p-deletion syndrome, show a higher penetrance with more severe phenotypes [ 10 ]. Based on our RNAseq data, down-regulation in CNTN1 , CNTN4 and CNTN5 is also present in cortical tubers to some degree, albeit to a lesser extent than CNTN3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, PTPRG has a precise distribution in the brain and is characteristic of a group of neurons [ 14 , 15 ]. Its high affinity for contactin members, which are involved in autism spectrum disorder (ASD), suggest a potential role in this disease [ 57 , 58 ]. Various evidence indeed suggesting PTPRG as a susceptible gene involved also in neuropsychiatric disorders.…”
Section: Participation Of Ptprg In Different Pathological Processesmentioning
confidence: 99%